36=13w-4w

Simple and best practice solution for 36=13w-4w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36=13w-4w equation:


Simplifying
36 = 13w + -4w

Combine like terms: 13w + -4w = 9w
36 = 9w

Solving
36 = 9w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-9w' to each side of the equation.
36 + -9w = 9w + -9w

Combine like terms: 9w + -9w = 0
36 + -9w = 0

Add '-36' to each side of the equation.
36 + -36 + -9w = 0 + -36

Combine like terms: 36 + -36 = 0
0 + -9w = 0 + -36
-9w = 0 + -36

Combine like terms: 0 + -36 = -36
-9w = -36

Divide each side by '-9'.
w = 4

Simplifying
w = 4

See similar equations:

| X+2=289 | | 10x=-4x+-7 | | -mn+7mp+10m=-2n-8 | | 3a^2+9a+30=0 | | 32=7k-3 | | 4n-6=2n-2n+2 | | X^2-10x-263=0 | | -(1+b)=-(3b-3) | | 2(9-4)+15=13 | | 2(50+-1.5y)+3y=100 | | 52-(2c+3)=4(3+7)+c | | 2(4-5x)=-15x+10 | | s^3-3s^2=5 | | -12p=240 | | 4(3v+7)= | | -100+4*90= | | 71-3x=51 | | 5x-3=2x+8+1 | | 2x+75=4x+91 | | 10z+8m-5z-2= | | -1=2x^2+2x^2+2 | | 7x+14=2x+2 | | -38v-114=-41v-321 | | x+1/2+x+2/3+x+3/4=16 | | 29=8y+(-3) | | t=3s+18.95 | | 13=6+1 | | -1=x^2-5x+2 | | 5x+(-9)=26 | | 1=24-5b | | 186+26b=16b-224 | | 4w+4X+13y+6w+8x-8y= |

Equations solver categories